An International Exploration of the Effect of Media Portrayals of Postconcussion Management on Concussion Identification in the General Public. Issue 3 (May 2020) - Ku, Cindy; McKinlay, Audrey; Grace, Randolph C.; Linden, Mark; McLellan, Tracey
Abstract : Background: Concussion portrayal in media broadcasts of sporting events may contribute to lack of public understanding regarding concussion. Methods: In total, 828 participants from Australia, New Zealand, and the United Kingdom completed a questionnaire assessing concussion knowledge. Participants were randomly assigned to either receive sports return-to-play (RTP) guideline information (RTP group) or not (no-RTP group). Participants viewed 12 short clips from televised rugby games and indicated whether they believed the player in each clip had sustained a concussion. Participants were then informed whether the player was removed, returned, or stayed in the game and again asked whether they thought a concussion had occurred. Results: Probability of reporting a likely concussion over all videos was 65.6%. When told a player's possible concussion was managed by removal from the game, participants were more likely to change their response from "no" (no concussion) to "yes" (concussion) than from "yes" to "no." When told the player stayed or returned to the game, participants were more likely to change their response from "yes" (concussion) to "no" (no concussion) than from "no" to "yes." There was no significant main effect for RTP guideline manipulation or interaction effect with RTP information. Conclusion: Additional player's injury management information influenced participants' judgments of concussion occurrence. Results show that information provided via sports media broadcasts influenced viewers' perceptions of concussion and appropriate concussion management.